Gods and beasts [large type] : a novel - Mina, Denise (Mina, Denise. Alex Morrow novel., 2013)
In the aftermath of an elderly man's murder during a holiday season bank robbery, DS Alex Morrow discovers that the bank's alarm system had been disabled before the robbery and uncovers a sinister political network that places the entire city at risk.